Pola Jaringan Korupsi di Tingkat Pemerintah Desa (Studi Kasus Korupsi DD dan ADD Tahun 2014-2015 di Jawa Timur) - Rahman, Fathur; Baidhowi, Achmad; Sembiring, Ruth Agnesia (Integritas : Jurnal Antikorupsi, 2018)
Cases of corruption are not done alone but formed a network in it. Social interaction will form an intense social network, where between individuals have strong bonds, especially family ties. The problem of corruption is not only in the central and local government level, but has already entered the village government sector. The case of DD and ADD corruption that occurred in Klebun Semar Paravan has the background and the relationship between the actors that escaped to be observed, why a network is so strong, especially the corruption that has formed a separate network.The dominant relationship in this case is family relations, the same profession of the religious network and the village chief's successful team. The pattern of leadership of the head of the garden will be the spotlight in running the wheels of his government because the dominant power so as to encourage the occurrence of corruption. Keywords:social networking, corruption, relationships between actors, power.